Self-harm among inmates of the Berlin prison system - Blees, Alexander; Jakobowitz, Sharon; Hofer, Jakob; Konrad, Norbert; Krebs, Julia; Opitz-Welke, Annette (Frontiers in Psychiatry, 2024)
Introduction Self-harming behavior in prisoners is a prevalent phenomenon, with international studies estimating a 4% prevalence rate. However, studies on self-injurious behavior in the German prison system are currently lacking. Therefore, our study aims to conduct an initial assessment. Methods The Criminological Service for the Berlin Prison System distributed questionnaires on incidents of self-harm to all Berlin prisons, except for juvenile detention centers. The questionnaires were supplemented with medical data, such as psychiatric diagnoses and medication. Results 62 questionnaires were returned, which could be attributed to 52 inmates. Compared to the average population in the Berlin prison system, the study sample exhibited variations in age, gender distribution and nationality. 94% of the inmates received a psychiatric diagnosis. Two-thirds of the male inmates had substance use disorders, while 83% of the female inmates had emotionally unstable personality resp. borderline disorders. Prior to self-harm, 87% of the inmates were administered psychiatric medication. Discussion Our study found similarities between the study population and international studies in the distribution of certain characteristics. We assume that many of the postulated risk factors can also apply to Berlin prisoners. However, the study is limited by the small number of cases and the absence of a control group.